Case report: Cystic fibrosis with kwashiorkor: A rare presentation in the era of universal newborn screening - Wolfe, Annemarie G.; Gilley, Stephanie P.; Waldrop, Stephanie W.; Olson, Christina; Harding, Emma; Widmer, Kaitlin; Gumer, Lindsey B.; Haemer, Matthew; Hoppe, Jordana E. (Frontiers in Pediatrics, 2023)
Background Universal newborn screening changed the way medical providers think about the presentation of cystic fibrosis (CF). Before implementation of universal screening, it was common for children with CF to present with failure to thrive, nutritional deficiencies, and recurrent infections. Now, nearly all cases of CF are diagnosed by newborn screening shortly after birth before significant symptoms develop. Therefore, providers often do not consider this illness in the setting of a normal newborn screen. Newborn screening significantly decreases the risk of complications in early childhood, yet definitive testing should be pursued if a patient with negative newborn screening presents with symptoms consistent with CF, including severe failure to thrive, metabolic alkalosis due to significant salt losses, or recurrent respiratory infections. Case presentation We present a case of a 6-month-old infant male with kwashiorkor, severe edema, multiple vitamin deficiencies, hematemesis secondary to coagulopathy, and diffuse erythematous rash, all secondary to severe pancreatic insufficiency. His first newborn screen had an immunoreactive trypsinogen (IRT) value below the state cut-off value, so additional testing was not performed, and his growth trajectory appeared reassuring. He was ultimately diagnosed with CF by genetic testing and confirmatory sweat chloride testing, in the setting of his parents being known CF carriers and his severe presentation being clinically consistent with CF. Acutely, management with supplemental albumin, furosemide, potassium, and vitamin K was initiated to correct the presenting hypoalbuminemia, edema, and coagulopathy. Later, pancreatic enzyme supplementation and additional vitamins and minerals were added to manage ongoing deficiencies from pancreatic insufficiency. With appropriate treatment, his vitamin deficiencies and edema resolved, and his growth improved. Conclusion Due to universal newborn screening, symptomatic presentation of CF is rare and presentation with kwashiorkor is extremely rare in resource-rich communities. The diagnosis of CF was delayed in our patient because of a normal newborn screen and falsely reassuring growth, which after diagnosis was determined to be secondary to severe edematous malnutrition. This case highlights that newborn screening is a useful but imperfect tool. Clinicians should continue to have suspicion for CF in the right clinical context, even in the setting of normal newborn screen results.